INITIAL TENSION IF THE PROCESS OF PROFESSIONALIZATION OF BRAZILIAN SOCCERABSTRACT (Fiep Bulletin - online, 2014)
In the first two decades of the XX century, soccer had already become an increasingly popular sport. It seems that the main dilemma at the time soccer was developing into professional sport was the loss of upper classes domain over this space. Part of club managers still had in mind that this was a place of cheerful and festive pastimes for wellborn people. Club associates sought activities that could reflect their lifestyle. When allowing the presence of players from the lower classes, they were giving up the place of refinement that the sport in general should observe. The process of changing the amateur status into professional created several tensions in the first decades of the XX century. The initial structural organization, designed to manage the sport among few upper class clubs, started to not to respond the demands posed by the other clubs -- the lower class ones--, mainly due to the increasing audience that paid to see the games and wanted to see a good show. The pressure that players of smaller clubs put on the managers caused discomfort and showed the need for new guidelines. Veblen (1974) discussed that the upper classes tended to impose part of their lifestyle upon the lower classes, however maintaining a structure of closure. Nevertheless, the pressure put on the upper classes forced the openness for the inclusion of lower classes into a higher status. Hirschman (1992) analyzed some social transformations that accompanied modernity and proposed three theses to argue the tension created by such changes: Perversity, Futility, Jeopardy. In this study, we have used Hirschman's theses to argue the tension between liberals and conservatives in the period in which this transformation was about to happen. On one hand, the defenders of professionalism, who believed in the sport development and the growing entertainment industry, and, on the other hand, the defenders of amateurism, who wished to maintain the aristocratic ideals. This article develops a reflection concerning this period of transformation.
Keywords: Soccer; amateurism; professionalism; history